2017
DOI: 10.1111/cen.13348
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing pre‐operative urinary calcium excretion in primary hyperparathyroidism

Abstract: In multivariable analysis, 1,25-(OH)2 D3 and osteocalcin were the only factors correlating with CCCR. Vitamin D3 replacement may therefore impair the diagnostic value of CCCR and increase the importance of close monitoring of urinary Ca excretion during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kaderli et al showed that the parameters affecting CCCR in subjects with PHPT were 1,25(OH)2D and osteocalcin. 12 Analyzing CCCR, 20.2% of the patients in our study showed evidence of FHH, 30.7% showed evidence of PHPT, and 49.1% were in the gray area. Unfortunately, CCCR was of little assistance in confirming diagnoses.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Kaderli et al showed that the parameters affecting CCCR in subjects with PHPT were 1,25(OH)2D and osteocalcin. 12 Analyzing CCCR, 20.2% of the patients in our study showed evidence of FHH, 30.7% showed evidence of PHPT, and 49.1% were in the gray area. Unfortunately, CCCR was of little assistance in confirming diagnoses.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, the evaluation of CCCR yielded 35 FHH (20.2%) and 53 PHPT (30.7%) suspected cases in our study group. Kaderli et al showed that the parameters affecting CCCR in subjects with PHPT were 1,25(OH)2D and osteocalcin …”
Section: Discussionmentioning
confidence: 99%